Indian cinema in retrospect - Film Seminar (1955 : Delhi, India); Ray, R. M.; Sangeet Natak Akademi (New Delhi) (New Delhi : Sangeet Natak Akademi ; Gurgaon : Hope India Publications, 2009)
Report of the Film Seminar, held at Delhi on 27th February 1955.
Originally published: 1956.
Keywords: Motion picture industry -- India; Motion pictures -- India -- History